Incidence of microplastic fiber ingestion by Common Terns (Sterna hirundo) and Roseate Terns (S. dougallii) breeding in the Northwestern Atlantic. (April 2022) - Caldwell, Aliya; Brander, Susanne; Wiedenmann, John; Clucas, Gemma; Craig, Elizabeth
Abstract: Ingestion of microplastics has been documented across marine species, but exposure remains sparsely described in many seabird species. We assess microplastic (between 0.2 and 5.0 mm) ingestion in two Northwestern Atantic - breeding species for which exposure to microplastics is entirely or largely undescribed: Common Terns ( Sterna hirundo ) and Roseate Terns ( S. dougallii ). Common Tern microplastic load did not vary between life stages ( p  = 0.590); microplastic load did differ in Common Tern adults breeding at two of three colonies explored ( p  = 0.002), with no other regional differences observed. Roseate Terns ingested significantly more microplastics than Common Terns ( p  = 0.007). Our results show that microplastic ingestion by terns varies regionally and interspecifically, but not by life stage, trends potentially explained by dietary differences. We provide the first quantification of microplastic fiber ingestion by terns in the Northwestern Atlantic and identify trophic dynamics related to microplastic ingestion, representing an important step toward understanding the risk of the pollutant to terns across regions, as well as toward the use of terns as potential bioindicators of microplastics. Highlights: 87.5% of fecal samples contained microplastic fiber loads higher than the average load found in controls. Common Tern microplastic fiber ingestion load varies among some spatially distinct colonies, but not all. Roseate Terns ingest more microplastic fibers than Common Terns. Microplastic fiber ingestion load does not vary between Common Tern life stages. Terns likely ingest microplastic fibers via secondary ingestion, suggesting diet may influence microplastic load.